EZH2 as a major histone methyltransferase in PDGF-BB-activated orbital fibroblast in the pathogenesis of Graves’ ophthalmopathy - Sopita Visamol; Tanapat Palaga; Preamjit Saonanon; Vannakorn Pruksakorn; Nattiya Hirankarn; P. Martin van Hagen; Willem A. Dik; Sita Virakul (Scientific Reports, 2024)
Abstract Graves’ ophthalmopathy (GO) is an extra-thyroidal complication of Graves’ disease which can lead to vision loss in severe cases. Currently, treatments of GO are not sufficiently effective, so novel therapeutic strategies are needed. As platelet-derived growth factor (PDGF)-BB induces several effector mechanisms in GO orbital fibroblasts including cytokine production and myofibroblast activation, this study aims to investigate the roles of histone lysine methyltransferases (HKMTs) in PDGF-BB-activated GO orbital fibroblasts by screening with HKMTs inhibitors library. From the total of twelve selective HKMT inhibitors in the library, EZH2, G9a and DOT1L inhibitors, DZNeP, BIX01294 and Pinometostat, respectively, prevented PDGF-BB-induced proliferation and hyaluronan production by GO orbital fibroblasts. However, only EZH2 inhibitor, DZNeP, significantly blocked pro-inflammatory cytokine production. For the HKMTs expression in GO orbital fibroblasts, PDGF-BB significantly and time-dependently induced EZH2, G9a and DOT1L mRNA expression. To confirm the role of EZH2 in PDGF-BB-induced orbital fibroblast activation, EZH2 silencing experiments revealed suppression of PDGF-BB-induced collagen type I and α-SMA expression along with decreasing histone H3 lysine 27 trimethylation (H3K27me3) level. In a more clinically relevant model than orbital fibroblast culture experiments, DZNeP treated GO orbital tissues significantly reduced pro-inflammatory cytokine production while slightly reduced ACTA2 mRNA expression. Our data is the first to demonstrate that among all HKMTs EZH2 dominantly involved in the expression of myofibroblast markers in PDGF-BB-activated orbital fibroblast from GO presumably via H3K27me3. Thus, EZH2 may represent a novel therapeutics target for GO.